Optimization of the Management of Student Mental Health Education in Colleges and Universities - Ding, Xiaoxi; Xue, Jinglan; Sun, Xiaodong; Fan, Yunting (Transactions on Social Science, Education and Humanities Research, 2023)
Research on the mental health of students in colleges and universities has a long history, and colleges and universities also pay attention to the mental health education of students while carrying out professional education. The rapid development of the mobile Internet has an increasingly significant impact on the student population in colleges and universities, and to a certain extent, it has an impact on the mental health of students. Therefore, the management of college students’ mental health education has become the focus of research in colleges and universities. In this context, this paper mainly analyzes the value of the era of mental health education in colleges and universities, and explores the dilemmas faced by the management of mental health education. In addition, strategies to strengthen the management of college students’ mental health education are proposed to promote the progress and development of higher education teaching management.